ChemInform Abstract: LiAlH4‐Promoted Tandem Reduction/Oxidation of Fluorenyl Derivatives under Air. Issue 13 (March 2015) - Matviiuk, Tetiana; Menendez, Christophe; Carayon, Chantal; Saffon, Nathalie; Voitenko, Zoia; Lherbet, Christian; Baltas, Michel
Abstract Since a 9‐hydroxyfluorenyl derivative such as (II) is observed as by‐product in the reduction of a pyrrolidine‐2, 5‐dione such as (I), the process is investigated in detail.